2021
DOI: 10.1177/09636625211048775
|View full text |Cite
|
Sign up to set email alerts
|

I am a scientist . . . Ask Me Anything: Examining differences between male and female scientists participating in a Reddit AMA session

Abstract: This article investigates interactions between scientists and the online community Reddit. Given that past research on computer-mediated communication between scientists and the public found that male scientists are typically more popular in online spaces than female scientists, we examined differences in popularity as well as potential gendered differences in communication style. Specifically, we examined 269 Reddit “Ask Me Anything” sessions as well as the comments linked with each session ( n = 125,580). Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In the current study, structural fluency is operationalized by readability, namely the Flesch Reading Ease metric (Flesch, 1948). Prior work has used readability indices to identify deception and obfuscation (Humpherys et al, 2011; Li, 2008; Markowitz et al, 2021; Markowitz & Hancock, 2016), the communication styles of male and female scientists in online settings (Hubner & Bond, 2022), and the helpfulness of online reviews (Fang et al, 2016). Readability is therefore an important indicator to evaluate the link between language and psychological dynamics, which is why it is evaluated as a key measure of structural fluency under conditions of instrumental goal activation.…”
Section: Processing Fluency and The Instrumentality Heuristicmentioning
confidence: 99%
“…In the current study, structural fluency is operationalized by readability, namely the Flesch Reading Ease metric (Flesch, 1948). Prior work has used readability indices to identify deception and obfuscation (Humpherys et al, 2011; Li, 2008; Markowitz et al, 2021; Markowitz & Hancock, 2016), the communication styles of male and female scientists in online settings (Hubner & Bond, 2022), and the helpfulness of online reviews (Fang et al, 2016). Readability is therefore an important indicator to evaluate the link between language and psychological dynamics, which is why it is evaluated as a key measure of structural fluency under conditions of instrumental goal activation.…”
Section: Processing Fluency and The Instrumentality Heuristicmentioning
confidence: 99%
“…Verbal structure is another indicator of complexity that is psychologically rich. Prior work has used readability indices, for example, to identify deception and obfuscation (Humpherys et al, 2011;Li, 2008;Markowitz & Hancock, 2016), the communication styles of male and female scientists in online settings (Hubner & Bond, 2021), and the helpfulness of online reviews (Fang et al, 2016). Readability is an important indicator to evaluate the relationship between fluency and psychological dynamics; the current work therefore explores how readability relates to petition support under conditions of instrumental goal activation.…”
Section: Verbal Complexity In Manymentioning
confidence: 99%
“…The underrepresentation of female scientists is also noticeable in popular culture. In most television programs, newspapers, films, and commercials, there are more male than female scientists ( Hubner and Bond, 2021 ; Steinke, 2017 ). A recent analysis of survey data from a large national sample of Italian academics identified that female scholars are actively involved in public engagement activities, but not in the most visible ones ( Anzivino, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These trends are present on social media platforms as well. Several studies that have monitored the presence of female scientists on various social networks, especially Twitter and Facebook ( Amarasekara and Grant, 2019 ; Demailly et al, 2020 ; Hubner and Bond, 2021 ; Ke et al, 2017 ; Klar et al, 2020 ; Mueller-Herbst et al, 2020 ), have reported mixed results. For example, a review by Ke et al (2017) identified that the ratio of female to male scientists on Twitter is actually better than the ratio of female to male scientists in academic publications.…”
Section: Introductionmentioning
confidence: 99%